The Influence of Leadership Style and Work Motivation on Employee Performance - Arifuddin, Arifuddin; Lita, Wang; Catherine, Sarkissian; Yingxiang, Schunk (Journal Markcount Finance, 2023)
This study aims to determine and analyze the effect of leadership style and work motivation on employee performance at the Regional Financial Management Agency, Sidenreng Rappang Regency. The analytical method used is Quantitative Analysis, namely data analysis in the form of numbers in the discussion, through statistical calculations based on the answers to the questionnaires from the respondents. The results of the calculation of the score or value are then used in statistical analysis carried out with the help of the SPSS program to prove the relationship and influence between research variables, using the following data test; Validity Test, Reliability Test, Classical Assumption Test and Regression Analysis; Y = a + b1 X1 + b2X2 Where :Y: Employee Performance, X1: Leadership style, X2: Work Motivation, a: Constants, b1b2: Regression Coefficient The results showed that: The results of hypothesis testing has proven that there is an influence between motivation and employee performance. Tests prove that motivation has a positive influence on employee performance. Judging from the calculations that have been done, the t-count coefficient is 1.902 with a significance level of 0.064. The significance level is greater than 0.05, which means that the hypothesis in this study rejects Ha and accepts Ho. The results of hypothesis testing have proven that there is an influence between leadership style and employee performance. Tests prove that leadership style has a positive influence on employee performance. Judging from the calculations that have been done, the coefficient value of t count is 2.538 with a significance level of 0.015. The yield significance level of 0.015 is smaller than 0.05, thus Ha is accepted and Ho is rejected. Motivation has the strongest influence on employee performance.